A systematic review of factors associated with service user satisfaction with psychiatric inpatient services. (September 2017) - Woodward, Sarah; Berry, Katherine; Bucci, Sandra
Abstract: Background: Satisfaction is seen as an indicator of the quality of mental health services and has been related to outcomes and compliance with treatment. The current review seeks to examine the factors relating to satisfaction with inpatient services. Method: A search was conducted of PsycInfo, Web of Science, Cinahl, Embase and Medline databases. Screening resulted in 32 papers being included in the review. Papers were subject to quality assessment using the Mixed Methods Appraisal Tool (MMAT). Results: Review of the included papers suggested factors relating to satisfaction could be broadly classified as either service user or service/ward related. Service user related factors included findings that satisfaction was higher when service users were admitted voluntarily. Service related factors included findings that satisfaction was negatively associated with experiences of coercion and positively associated with being on an open ward. Conclusion: It appears that coercion has a key role in ratings of satisfaction. Additionally, service users reported an impact of staff relationships, and the ward environment. Satisfaction is associated with a range of factors, an awareness of which will allow for the development of quality services that meet the needs of service users.